Estudo da demanda evapotranspirométrica do munícipio de Vitória da Conquista/bBA - Santos, Lucas da Costa [UNESP]; Zocoler, João Luis [UNESP]; Bezerra, Adma Viana [UNESP]; Justi, André Luiz; Carvalho, José Joaquim de (My University, 2011)
The objective of this study, was estimate and analyze the demand evapotranspirometers of Vitoria da Conquista city, located in the southwestern state of Bahia/Brazil, and assess the performance of empirical methods of Modified Penman - FAO 24, Radiation - FAO 24 Blaney -Criddle - FAO 24, Samanni-Hargreaves (1985), Priestley-Taylor and Turc (1961), which were compared with the standard PenmanMonteith - FAO 56, on scales of one, three, five and seven days. Climatic variables were used for the period 1997 to 2010. To compare the values of ET0 estimated by the empirical equation and the standard method, were considered the parameters of the regression equation a and b, coefficient of determination (r²), correlation coefficient (r), estimated standard error (ESE) agreement index (d) and the index of confidence or performance (c). The results indicate that for purposes of design and management of irrigation systems in the region of Vitoria da Conquista, Bahia/Brazil one must adopt a value of up to 8 ET0 mm day-1 , a value determined by the method of Penman Monteith - 56 FAO for the period 1997 to 2010. For other methods, all performed quite well with ratings ranging from Very Good to Great for the climatic conditions of the city under study.

Objetivou-se com este trabalho, estimar e analisar a demanda evapotranspirométrica do município de Vitória da Conquista, localizado na região sudoeste do Estado da Bahia, e ainda avaliar o desempenho dos métodos empíricos de Penman Modificado – FAO 24, Radiação – FAO 24, Blaney-Criddle - FAO 24, Hargreaves-Samanni (1985), Priestley-Taylor e Turc (1961); os quais foram comparados com o método padrão Penman-Monteith – FAO 56, nas escalas de um, três, cinco e sete dias. Foram utilizadas variáveis climáticas referentes ao período de 1997 a 2010. Para comparar os valores de ET0 estimados por meio das equações empíricas com os do método padrão, foram considerados os parâmetros da equação de regressão a e b, coeficiente de determinação (r²), coeficiente de correlação (r), estimativa do erro padrão (EEP), índice de concordância (d) e do índice de confiança ou desempenho (c). Os resultados obtidos indicam que para fins de dimensionamento e manejo de sistemas de irrigação na região de Vitória da Conquista/BA, deve-se adotar um valor de ET0 máxima de 8 mm dia-1 ,valor este determinado pela metodologia de Penman Monteith – FAO 56 para o período de 1997 a 2010. Quanto às demais metodologias, todas apresentaram comportamento satisfatório com classificação variando de Muito Boa a Ótima para as condições climáticas do município em estudo.
Study of evapotranspirometer demand the city of Vitoria of Conquista, Brazil
Keywords: Climate variables; Empirical equation; Reference evapotranspiration; Variáveis climáticas; Equações empíricas; Evapotranspiração de referência